Потокові моделі безпечної та відмовостійкої маршрутизації з балансуванням навантаження в програмно-конфігурованих телекомунікаційних мережах - Шаповалова, А. С. (ХНУРЕ, 2021)
Дисертаційна робота присвячена вирішенню актуальної науково-прикладної задачі, що полягає в забезпеченні відмовостійкості та мережної без-пеки в програмно-конфігурованих ТКМ, які функціонують в умовах відмов та компрометації мережного обладнання, шляхом розроблення та вдосконалення відповідних математичних моделей маршрутизації. Удосконалено та дослі-джено потокову модель безпечної маршрутизації в телекомунікаційних ме-режах. Удосконалено та досліджено потокову модель безпечної маршрутиза-ції з балансуванням навантаження на основі врахування параметрів мережної безпеки в програмно-конфігурованих телекомунікаційних мережах. Уперше запропоновано та досліджено модель швидкої перемаршрутизації із забезпе-ченням балансування навантаження на принципах Traffic Engineering та ди-ференційованого обмеження трафіку в програмно-конфігурованих телекому-нікаційних мережах. Удосконалено та досліджено потокову модель безпечної швидкої перемаршрутизації з балансуванням навантаження та диференційо-ваним обмеженням трафіку на границі телекомунікаційної мережі. The dissertation is devoted to solving the relevant scientific and applied problem, which is to ensure fault tolerance and network security in software-defined telecom-munication networks, which operate in conditions of failure and compromise of net-work equipment, by developing and improving appropriate mathematical models of routing. As a result of the analysis it was found that improving the efficiency of solutions for secure and fault-tolerant routing requires appropriate improvement of existing and development of new mathematical models and methods based on adequate considera-tion of information about the state of the telecommunications network: network to-pology, packet flow characteristics, communication bandwidth and indicators net-work security elements (nodes and links). The flow-based routing model has been improved, taking into account infor-mation security risks using base score metrics of criticality vulnerabilities. The novel- ty of the developed model is that the calculation of route metrics uses expressions that, in accordance with the recommendations of NIST CVSS v.3, characterize the risk of information security in the communication channels of the telecommunica-tions network. The use of the proposed model of secure routing allows to calculate and use routes with minimal risk of information security, thus ensuring the maximum level of network security for packets transmitted in the telecommunications network. The flow-based model of secure routing with load balancing under network se-curity parameters in software-defined telecommunication networks has been im-proved. The novelty of the proposed model is the modification of load balancing conditions in telecommunication network, which focus on minimizing the upper bound of the network links utilization, weighted by the probability of their compro-mise. The use of the proposed model allows to take into account both the bandwidth of communication links and their security parameters, represented by the probabilities of compromise when determining the order of load balancing. For the first time, a model of fast rerouting with load balancing based on the principles of Traffic Engineering (TE) and differentiated traffic policing in software-defined telecommunication networks has been proposed. The novelty of the model is that, firstly, the conditions of flow conservation have been modified, take into ac-count the traffic priority policing at the network edge in case of its probable overload, caused by load increase; and secondly, a system of criteria for optimization of route solutions is proposed, the use of which focuses on minimizing the upper bound of communication links utilization and denials of service at the network edge, weighted on the priority and intensity of flows to prevent congestion. The flow-based secure fast rerouting model with load balancing and differentiat-ed traffic policing in software-defined telecommunication networks has been im-proved. The novelty of the model is to ensure the protection of elements (nodes, links, routes) of the network and its bandwidth in the process of fast rerouting based on the probability of compromising communication links, and in the case of differentiated traffic policing at the network edge ensuring the requirements of packet flows regard-ing the level of network security.
Keywords: потокова модель; мережна безпека; відмовостійкість; безпечна маршрутизація; швидка перемаршрутизація; ризик інформаційної безпеки; базові метрики; критичність вразливостей; балансування навантаження; диференційоване обмеження трафіку; flow-based model; network security; fault tolerance; secure routing; fast rerouting; information security risk; basic metrics; criticality vulnerabilities; load balancing; differentiated traffic policing